Control engineering solutions a practical approach - Albertos Pérez, P.; Strietzel, R. (Roland); Mort, N. (Neil) (Institution of Electrical Engineers, 1997)
The book reviews development in the following fields: process model identification; analogue controller design; classic controller design; integral wind-upl; unstable systems control; temperature control; heat flow rate control; inverted pendulum control; disturbance rejection; multivariable process control; predictive control; PID control; state-space adaptive control; distributed process control; fuzzy control; adaptive control supervision; model based fault detection; microcomputer based implementation and software design.